Solar Tunnel Drying System: A Literature Review - Barooah, Manas Jyoti; Sethi, Laxmi Narayan; Borah, Abhijit (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2020)
AbstractProduction, productivity, and area under production from fruits and spices are gradually increasing. Improper processes of freshly harvested spice and fruit products will make them undergo qualitative deterioration with each passing hour. This deterioration is more pronounced in high humid areas. Drying process in one or the other form is essential. Freshly harvested spices and fruit products in average contain more than 80% moisture. The commodities need to be dried to have a moisture content below 10% in the shortest possible time for safe storage. Drying process in most cases are accomplished by the open sun. Meanwhile, the environmental condition in solar tunnel drying is enclosure type and the product is protected from rains, dust, insects, and rodents. Solar tunnel drying, a widely used bulk dryer, facilitates faster drying than open drying by virtue of the greenhouse effect. Commercial cultivators by and large choose faster drying methods using wood and fossil fuel-fired heating sources. This study attempts to review recent advances of various designs and working of the greenhouse drying system in totality, like auxiliary drying during off-sun hours, bulk drying feasibility, ease in loading and unloading along with an analysis of key features and economics involved.Keywords: auxiliary drying, greenhouse drying system, processing AbstrakProduksi, produktivitas dan luas areal produksi buah-buahan dan rempah-rempah meningkat secara bertahap. Produk rempah dan buah yang baru dipanen akan mengalami penurunan kualitas seiring waktu berjalan jika tidak diproses dengan benar. Kerusakan ini lebih terlihat di daerah dengan kelembaban tinggi. Pengeringan dalam satu atau bentuk lain penting dalam pemrosesan. Rempah-rempah dan produk buah yang baru dipanen rata-rata mengandung lebih dari 80% kelembaban dan perlu dikeringkan hingga kelembabannya di bawah 10% dalam waktu sesingkat mungkin untuk penyimpanan yang aman. Pengeringan ini dalam kebanyakan kasus dilakukan dengan sinar matahari terbuka, sedangkan kondisi lingkungan pengeringan terowongan surya adalah tipe tertutup dan produk terlindungi dari hujan, debu, serangga dan hewan pengerat. Pengeringan terowongan surya merupakan pengering kapasitas besar yang banyak digunaka. Pengeringan dengan alat ini lebih cepat daripada pengeringan terbuka berdasarkan efek rumah kaca. Pembudidaya komersial pada umumnya memilih metode pengeringan yang lebih cepat yang menggunakan kayu dan sumber pemanas berbahan bakar fosil. Studi ini bertujuan untuk meninjau kemajuan terkini dari berbagai desain dan cara kerja sistem pengeringan rumah kaca secara keseluruhan, seperti, pengeringan tambahan di malam hari, kelayakan pengeringan kapasitas besar, kemudahan dalam bongkar muat, serta analisis fitur utama dan ekonomi.Kata kunci: pengeringan bantu, pengolahan, sistem pengeringan rumah kaca